The Future of Research and Experimentation in Technological Design of the Relationships between Architecture, Energy and Environment - Angelucci, Filippo (Journal of Technology Innovations in Renewable Energy, 2018)
The problematic nature of the centrality of the focal core formed of the Technological Design/ Energy / Environment relationship has never been so evident as at the present time, together with the need to tackle it urgently. Humanity has been directly interfacing with the energy issue and the "non-renewability" of resources on the one hand, and the question of harmful and climate-changing emissions on the other part for other for at least thirty years. This is the reason why it is our principal scientific and ethical duty to focus a major part of our attention and efforts on research – as proved in Italy by a significant part of the activities of PhD Program in "Planning Design Technology" of Sapienza University of Rome, by "NZEB" cluster of SITdA Italian Society of Technology of Architecture and by National Work Group "Green Economy for Architecture and Cities" of CNGE National Council on the Green Economy â€“ in order to take significant steps forward. And to provide incisive answers for the emergency situations represented by, to use the two iconic terms of the much larger set of questions, the Climate and Energy problems. On the other hand, if it is true that the Nearly Zero Energy Building slogan specifically alludes to the scale of action, what is certain is that, at an international level, this is not the sole correct level on which we can and we must operate in order to have a chance of success, effectiveness and obtainment of that efficiency referred to in the first European directive 2002/91/EC through to the most recent 2010/31/EU "Energy Performance of Buildings" and 2012/27/EU "Energy Efficiency" which, inter alia, establish the concept of NZE architecture. So the working dimension becomes primarily "a-scaleable", in its need to oscillate constantly, with ongoing feedback, between actions at various leveles. Research related to the broad areas of Nearly Zero Energy Architecture developed in recent years fits into Technological Design in this sense and in this light, mainly in relation to regeneration of the existing architectural heritage, technologies for new building projects, process governance, the systemic approach on an urban scale, environmental and energy sustainability protocols, smart communities and cultural heritage.